2021
DOI: 10.1007/s40171-021-00280-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between “Job Satisfaction” and “Job Performance”: A Meta-analysis

Abstract: The purpose of this meta-analytic research is to obtain a clear and unified result for the relationship between job satisfaction and job performance, as previous research has shown contradictions in this regard. A total of 913 articles in both English and Persian languages were obtained from four databases, and finally, 113 articles with 123 independent data were selected and analyzed. The random-effects model was adopted based on results, and the analysis resulted a medium, positive, and significant relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 172 publications
3
30
0
2
Order By: Relevance
“…Research on the relationship between job satisfaction and productivity is abundant. The meta-analysis conducted by Davar and RanjuBala (2012) and Katebi et al 2022 found that their relationship was only in the medium category. In other words, there are variations in the relationship between the two variables from low to high.…”
Section: Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the relationship between job satisfaction and productivity is abundant. The meta-analysis conducted by Davar and RanjuBala (2012) and Katebi et al 2022 found that their relationship was only in the medium category. In other words, there are variations in the relationship between the two variables from low to high.…”
Section: Workmentioning
confidence: 99%
“…The meta-analysis by Davar and RanjuBala (2012) and Katebi et al (2022) found that job satisfaction positively affects work productivity. This relationship is also proposed as the third hypothesis.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Every organization seeks to create satisfied employees to manage the organization's competence. However, the total organizational performance depends on the well-organized and valuable performance of individual employees of the organization (Katebi et al, 2022). Prior research has linked job satisfaction and job performance with different sectors.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Job satisfaction is a pleasure derived from a job (Javanmardnejad et al, 2021). It is one of the supervisor's significant challenges to ensure that their subordinates are satisfied with their jobs (Katebi et al, 2022). It was always considered that a satisfied employee is always more effective, efficient, and productive than a dissatisfied employee (Nguyen & Malik, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%